An Enhanced Elliptic Curve Cryptography Scheme for Secure Data Transmission to Evade Entailment of Fake Vehicles in VANET - Patil, Mayur Jagdish; Adhiya, Krishnakant P. (Cybernetics and systems, 2024)
Vehicular Ad-hoc Networks (VANET) help to increase traffic safety, manageability, and efficiency. VANET facilitates effective communication in the vehicular nodes. Here, the network attack is one of the significant consequences of VANET, which may affect network security. The high mobility of the nodes may become difficult to transfer the data through the vehicle. In this article, a novel method of Elliptic Curve Cryptography (ECC) is proposed. The key is generated by Key Generation Unit (KGU), and also the key is fed into the Road Side Unit (RSU). The keys in Enhanced ECC (EECC) are optimized using the Adaptive Horse herd Optimization Algorithm (AHOA). During decryption, the key of source node K1 is to be taken from RSU, where the key is processed by the Digital Signature method to obtain EECC key K2. With the generated K2, the destination node can retrieve the data by the proposed model. Thus, the simulation analysis of the proposed AHOA-EECC method has attained less time complexity which was compared against the high value of 5%, 12.4%, 50%, and 13.7% for GWO-EECC, PSO-EECC, AOA-EECC, and HOA-EECC. Finally, the outcome of the proposed system enhances the security level and performs better data transmission.